Oxidized corn oil changes the liver lipid metabolism of broilers by upregulating peroxisome proliferators activate receptor-α - Zhang, Yuqing; Mahmood, Tahir; Wu, Yuqin; Tang, Zhenhai; Wang, Youli; Wu, Wei; Zhou, Huajin; Guo, Yuming; Yuan, Jianmin (Poultry science, 2023)
The objective of the following study was to investigate the effects of naturally oxidized corn oil on the antioxidant capacity and lipid metabolism of broilers. A total of 450, 1-day-old Arbor Acres male broilers were randomly divided into 5 treatments with 6 replicate cages and 15 birds/cage. The dietary treatment array consisted of ratios of naturally oxidized corn oil to non-oxidized corn oil from 0:100, 25:75, 50:50, 75:25, and 100:0, respectively. Serum, liver, and abdominal fat samples were taken at 42 d. The results showed that the liver organ index, liver catalase (CAT) activity, malondialdehyde (MDA) content, and the serum aspartate aminotransferase (AST) content had significant quadratic relationships with the ratio of naturally oxidized corn oil (P < 0.05). Inflammatory infiltrating cells appeared in the liver of the 50% and 75% oxidized corn oil group. The percentage of abdominal fat, and serum free fatty acids (FFA) content increased linearly with the increased proportion of oxidized corn oil (P < 0.05). The mRNA expression of NADH quinone oxidoreductase 1 (NQO-1), nuclear factor kappa B (NF-κB), toll-like receptor-4 (TLR-4), peroxisome proliferators activate receptor-α (PPARα), carnitine acyltransferase (CPT1), and acyl-coenzyme oxidase (ACO) of the liver increased linearly while oxidized corn oil increased in the diet (P < 0.05). Diets containing 100% oxidized corn oil significantly changed the mRNA expression of liver Caveolin compared with other treatment groups (P < 0.05). Taken together, this study demonstrated that naturally oxidized corn oil could change liver lipid metabolism and accelerate lipid deposition of broilers by upregulating PPARα.